Effect of sinusoidal function on backpropagation learning - Karimi, B.; Ashenayi, K.; Seyed, T.B. (Proceedings of the 25th Annual Symposium on Simulation, ANSS 1992, 1992)
The backpropagation method is modified by replacing sigmoid function by sinusoidal function. The leaving law is also modified. The modified procedure shows great improvement over the original BP in terms of the number of neurons and the learning time. © 1992 IEEE.
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Proc. Annu. Symp. Simul., ANSS
Keywords: Backpropagation; Backpropagation learning; Circuit simulation; Learning time; Sigmoid function; Sinusoidal functions; Software engineering; dept.csc